(Lack of) knowledge of mothers about sickle cell trait and disease: a qualitative study - Rafael Rocha; Tania Vignuda de Souza; Rita de Cássia Melão de Morais; Luciana de Cássia Nunes Nascimento; Leila Leontina do Couto; Iraína Fernandes de Abreu Farias (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to analyze the understanding of mothers about sickle cell disease and/or trait of the family from a diagnosed child. Methods: this is a qualitative study, using a semi-structured interview with 23 mothers, at a sickle cell disease outpatient clinic of a public institution, from October to December 2017. Analysis was thematic. Results: all participants had sickle cell trait as well as the parents of their children. Twenty children were diagnosed with sickle cell disease by Heel Prick Test, and three, after hospitalization due to the disease. Most did not know how to report the presence of the trait or disease in relatives other than nuclear. Final considerations: diagnosis cannot be restricted to the result of neonatal screening, requiring that preventive information on sickle cell crises be reinforced. It is recommended to search for other affected relatives to learn about their genetic condition, reflecting on their reproductive decisions.